Manajemen Seleksi pada Posisi Education Administrator di Global Art Education Denpasar - Melissa Waturandang; Aljuanika Ertamaya Ering; Hana Wulandari Mona (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT. In the development of the world of education, education management is needed, one of which is the placement of human resources. Global Art as one of the companies engaged in the world of education requires Education Administrator staff for this reason, employee selection is carried out to fulfill the administrator position. In the selection, selection is carried out using the psychological test method or psychological examination. The research was conducted to find out how education management uses psychological tests in placing employees according to needs. Psikotest results found that prospective employees meet the requirements for the position of Education Administrator at Global Art